Pelatihan Pembuatan Pupuk Organik Cair Dari Kulit Pisang Ambon Pada Ibu-Ibu Dasawisma Dahlia Kelurahan Labuhan Ratu, Bandar Lampung - Yulianty; Endang Nurcahyani; Bambang Irawan; Salman Farisi; Suratman Umar; Enur Azizah (CV. Multi Kreasi Media, 2025)
One type of household waste that is commonly discarded and rarely reused is banana peel waste. If left unmanaged, it can cause environmental problems in both rural and urban areas. An alternative solution is to utilize banana peel waste, such as Ambon banana peels, as a source of local microorganisms for producing liquid organic fertilizer (POC). POC is relatively easy to produce and environmentally friendly. This community service program aimed to empower residents of Dasawisma Dahlia RT 004, Labuhan Ratu, Bandar Lampung, through training on the production of liquid fertilizer concentrate (LFC) from Ambon banana peels. The results showed an increase in participants’ knowledge and skills, as reflected in the average pre-test score of 60.51, which increased to 86.67 after the post-test. This represents an improvement of 26.15 points, or a 43.22% increase. The sustainability of this initiative lies in the potential for large-scale POC production, which can be further utilized for environmental and economic benefits.